Structure and Performance of the Service Sector in Transition Economies - Fernandes, Ana M. (2012)
This paper examines the performance of the service sector in the Eastern European transition economies during the 1997-2004 period. The performance of the service sector as a whole and of its sub-sectors is very heterogeneous within the region. Service sub-sectors that are information and communications technology producers or users and those using skilled labour more intensively exhibit the highest labour productivity growth. Our estimates show a positive and significant effect of liberalization on service labour productivity growth that is stronger for sub-sectors that are more distant from the technological frontier. Service liberalization is also shown to have a positive effect on labour productivity levels and growth of downstream manufacturing industries.